An Idea of Italianness in the World: Michela Murgia and Her Works Across Borders (Altre Modernità, 2025)
Translated into twenty-eight languages and countries, from South Korea to Brazil, Turkey and Iran, Michela Murgia has established herself as one of the most translated Italian writers of the XXI century. If in Italy her figure has been conceived and defined, even after her death, as a hybrid between writer and militant activist, abroad Murgia has mostly been identified as the narrator of a regional, geo-local Italy. Her works and the peritests of her translated books speak of an Italianness that is the bearer of local characters, typical of the imagination nurtured across the border towards Italy. The aim of the paper is to conduct a survey of Murgia’s foreign editions and to analyse the textual characteristics of her works to understand the features of the Italianness represented and received. A significant part of the work focuses on Accabadora, which alone constitutes forty of Murgia’s seventy foreign editions, with a focus on the reception in English-speaking countries.
Keywords: Michela Murgia; Accabadora; Italian literature; geolocal